Sejarah Kesultanan Bilah pada Masa Kolonial Belanda, 1865-1942 - Rambe, Sabda Firmansyah; Rohani, Laila; Batubara, Abdul Karim (Mahesa Research Center (PT. Mahesa Global Publishing), 2022)
This article discusses the history and development of the Bilah Sultanate which is currently located in Labuhanbatu Regency. This sultanate is one of the influential sultanates in the East Sumatra region, especially Labuhanbatu. This sultanate became the conquered territory of the Siak Indrapura Sultanate which was supported by the Dutch. This article uses a historical research method with four steps, namely: heuristics, criticism, interpretation, and historiography. The author's data collection was done by directly visiting the locations of the former areas of the Bilah Sultanate, interviews with traditional leaders and descendants, as well as written data from archives, books, journals and so on. The results showed that the Sultanate of Bilah had a period of prosperity as a result of its cooperation with the Dutch Colonial. Plantation investments made by European businessmen in the Labuhanbatu region and its surroundings were the reason this sultanate became so prosperous. However, because of its proximity, the Sultanate of Bilah also became a victim of the ferocity of the anti-feudalism (social revolution) movement in 1946 which targeted the Malay aristocrats in East Sumatra. The tragedy marked the end of the existence of the Blade Sultanate in the Labuhanbatu region.